2010
DOI: 10.1017/s1751731109990784
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the greenhouse gas balance of ruminant production systems through carbon sequestration in grasslands

Abstract: Soil carbon sequestration (enhanced sinks) is the mechanism responsible for most of the greenhouse gas (GHG) mitigation potential in the agriculture sector. Carbon sequestration in grasslands can be determined directly by measuring changes in soil organic carbon (SOC) stocks and indirectly by measuring the net balance of C fluxes. A literature search shows that grassland C sequestration reaches on average 5 6 30 g C/m 2 per year according to inventories of SOC stocks and 2231 and 77 g C/m 2 per year for draine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
289
1
38

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(361 citation statements)
references
References 116 publications
13
289
1
38
Order By: Relevance
“…Grasslands and potential for GHG reduction Grasslands can potentially offset a major proportion of the global emissions of GHG due to livestock (Soussana et al, 2010). These GHG are derived primarily from emissions of enteric methane by ruminants, to a minor extent from nitrous oxide produced from excreta, indirectly from production of grain crops for animal feedstuffs and from deforestation to create new pastures (FAO, 2009).…”
Section: The Multifunctional Roles Of Grasslandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grasslands and potential for GHG reduction Grasslands can potentially offset a major proportion of the global emissions of GHG due to livestock (Soussana et al, 2010). These GHG are derived primarily from emissions of enteric methane by ruminants, to a minor extent from nitrous oxide produced from excreta, indirectly from production of grain crops for animal feedstuffs and from deforestation to create new pastures (FAO, 2009).…”
Section: The Multifunctional Roles Of Grasslandsmentioning
confidence: 99%
“…Storage of C is higher under extensive management and low grazing pressures providing that soil nutrients are not limiting (Soussana et al, 2010). In a meta-analysis involving trials from 19 global grazing land regions, Follett and Schuman (2005) observed a general positive relationship between the C sequestration rate and the animal stocking density as livestock per hectare, the latter being obviously directly associated with pasture primary productivity.…”
Section: The Multifunctional Roles Of Grasslandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of grassland to sequester carbon has also been put forward as a key strategy to partly mitigate GHG emissions from the livestock sector (Soussana et al, 2010). Jones and Donnelly (2004) noted that carbon sequestration rates for permanent grasslands ranged from 0.2 to 0.6 tonnes carbon/ha per year (equivalent to 0.7 to 2.2 tonnes CO 2 e/ha per year) according to management, while the conversion from arable to grassland significantly increased carbon sequestration to 8 tonnes carbon/ha per year (29 tonnes CO 2 e/ha per year).…”
Section: Mitigation Strategies To Reduce Ghg Emissionsmentioning
confidence: 99%
“…Soussana et al (2010) also argued that soil carbon sequestration is reversible and vulnerable to disturbance, biodiversity loss and climate change.…”
Section: Mitigation Strategies To Reduce Ghg Emissionsmentioning
confidence: 99%